2011
DOI: 10.1016/j.ejvs.2011.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Reprinted Article “Carotid Artery Plaque Composition—Relationship to Clinical Presentation and Ultrasound B-mode Imaging”

Abstract: Ultrasound B-mode characteristics are related to the histological composition of carotid artery plaques and to patient's history. These results may imply that patients with distant symptoms may be regarded and treated as asymptomatic patients whereas asymptomatic patients with echolucent plaques should be considered for carotid endarterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Many studies have shown that visual classification is a feasible and reliable method for classification of ultrasound plaques with different echogenicity [ 12 , 13 , 33 ]. Geroulakos et al classified 70 carotid plaques into five different types (type 1 uniformly echolucent, type 2 predominantly echolucent, type 3 predominantly echogenic, type 4, uniformly echogenic, and type 5 calcified plaques) and the between-observer reproducibility was 85.71% ( κ = 0.79).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that visual classification is a feasible and reliable method for classification of ultrasound plaques with different echogenicity [ 12 , 13 , 33 ]. Geroulakos et al classified 70 carotid plaques into five different types (type 1 uniformly echolucent, type 2 predominantly echolucent, type 3 predominantly echogenic, type 4, uniformly echogenic, and type 5 calcified plaques) and the between-observer reproducibility was 85.71% ( κ = 0.79).…”
Section: Discussionmentioning
confidence: 99%
“…Mayor et al analyzed 95 carotid bifurcation plaques with the same five-type classification system, and a between-observer reproducibility of 91% ( κ = 0.87) was observed. In this study, the plaques were classified into three different types (type 1 echo-rich, type 2 intermediate and type 3 echolucent) according to the scheme of the European carotid plaque study group [ 12 ], and a higher between-observer reproducibility of 96.15% ( κ = 0.942) was achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperechoic plaques have a dense fibrosis layer and calcification creating a sound shape. [ 18 ] The hypoechoic and heterogeneous plaques are associated with neurovascular and cerebral ischemic symptoms. [ 19 ] In assessing the percentage of rSO 2 performed separately for each hemisphere with the left and right carotid arteries, it was determined that there was no significant difference in the mean rSO 2 of the right side of the brain in terms of carotid plaque status (the presence of plaque in the left and right carotid arteries) before and after induction, and during PDA graft and at the time of performing partial clamp, while the difference was significant at the time of performing LAD graft ( P = 0.001) and CX graft ( P = 0.020).…”
Section: Discussionmentioning
confidence: 99%